Chaotic oscillations in a model of suspended elastic cable under planar excitation - Szemplińska-Stupnicka, Wanda; Tyrkiel, Elżbieta; Zubrzycki, Andrzej (Computer Assisted Methods in Engineering and Science, 1999)
The single mode equation of motion of a suspended elastic cable under planar excitation is considered, and numerical exploration is focused on the chaotic oscillations which occur in a certain domain of system control parameters. Bifurcations of the subharmonic resonance oscillation and their evolution into chaotic attractor are studied. Then the global bifurcation theory is applied to determine the critical system parameters for which the chaotic attractor undergoes the subduction destruction in the "boundary crisis" scenario. The post-crisis transient motion, which in this case becomes the generic long-lasting chaotic system response, is also studied.